Constrictive pericarditis in a patient with sinus venosus atrial septal defect and anomalous right upper pulmonary venous return - Uppu Santosh; Chandrasekaran Sruti; Mallula Kiran (Wolters Kluwer Medknow Publications, 2009)
This is a report of a 49-year-old male, who presented with typical signs and symptoms of constrictive pericarditis. He was diagnosed with sinus venosus atrial septal defect (ASD) and anomalous right upper pulmonary venous return during his adolescence, which was elected not to be repaired. During the attempted repair of the ASD it was noted there was a thick fibrous material covering the heart, which had progressed over time leading to frank constrictive pericarditis. His ASD spontaneously closed over time. There have been less than 10 cases reported with constrictive pericarditis of nonsurgical etiology in a patient with ASD, and none with sinus venosus ASD.